A qualitative mystery shopper study that de(codes) the experiences of English and Spanish-speaking patients who call to schedule a first-time primary care appointment in the Los Angeles, Houston, and New York Metropolitan Statistical Areas - Esmeralda Melgoza; Ahmad Ismail; Lucía Félix-Beltrán; Rosario Majano; Arturo Vargas Bustamante (SSM: Qualitative Research in Health)
Objective: To qualitatively assess the experiences that English and Spanish-speaking patients with Medicaid managed care encounter when scheduling a first-time primary care appointment, with a preference for telehealth, in the Los Angeles (LA), Houston and New York (NY) Metropolitan Statistical Areas (MSAs). Methods: A list of primary care offices was created by scraping online directories from each managed care organization (MCOs) health plan operating in the three MSAs. Primary care offices were randomly selected to participate in this qualitative mystery shopper study. Two researchers listened and transcribed real-time calls between the mystery shopper patients and the receptionists at the primary care offices. Data collection occurred between April 8, 2024, and April 26, 2024, on different days and times of the week. Both researchers completed tests to calculate the Kappa statistic, which indicated substantial inter-rater agreement. The researchers then inductively coded the transcripts using thematic analysis on Dedoose version 9.2.012. Results: Our study suggests that Spanish-speaking patients who call to schedule a first-time primary care appointment are more likely to experience call transfers, be told to call back later, and encounter more telephone hang-ups, compared to English-speaking patients. Telehealth for first-time appointments is uncommon and typically available only under special circumstances, including COVID-19, medication refills, test result reviews, and for chronically ill populations. Conclusion: This study shows disparities in access to care between English and Spanish-speaking patients at the time of scheduling a first-time appointment, highlighting an important point for future intervention.